Analysis of Recruitment, Performance Evaluation, and Career Planning to Support Employee Performance - Candra, Primadi; Putri Amanda, Anggita; Gupron (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this study is to prove that there is a relationship between the dependent and independent variables. A literature review method was used to prepare this article, which analyzes previous studies without distributing questionnaires to respondents. The result of this study is the association of all independent and dependent variables. It can be concluded that the performance of an organization can only be successfully produced if the attitude is in line with the standards set by management. Periodic performance reviews are conducted to determine goal achievement and appropriate career plans. Increase employee motivation to increase productivity. In this literature review, we found that there is a large influence between variables, which can serve as a reference for research in the field of human resources.